Intercultural Gaps Between Indonesia and China on the Belt and Road Initiative: Causes and Remedies - Paulus Rudolf Yuniarto (China Quarterly of International Strategic Studies, 2019)
In implementing the Belt and Road Initiative (BRI), there remains a huge perception gap between China and Indonesia. Differences in ideology, politics, race, religion, and ethnicity are hindering the great potential of the BRI from being fully realized. To bridge the gap and enhance mutual understanding, people-to-people exchange between both countries should be accorded greater significance. In addition, strengthening bilateral cooperation in education, labor, tourism, and culture can bring positive spill-over effects beyond basic intercultural learning. Such non-infrastructure cooperation creates more room for people-to-people bonds to flourish, where economic interests are not blindly pursued. Deepened mutual understanding will, in turn, help achieve the major goals of the BRI and promote the building of a community of shared future along the route.